2004
DOI: 10.1016/j.febslet.2004.07.061
|View full text |Cite
|
Sign up to set email alerts
|

Role of amino‐acid residue 95 in substrate specificity of phosphagen kinases

Abstract: The purpose of this study is to elucidate the mechanisms of guanidine substrate specificity in phosphagen kinases, including creatine kinase (CK), glycocyamine kinase (GK), lombricine kinase (LK), taurocyamine kinase (TK) and arginine kinase (AK). Among these enzymes, LK is unique in that it shows considerable enzyme activity for taurocyamine in addition to its original target substrate, lombricine. We earlier proposed several candidate amino acids associated with guanidine substrate recognition. Here, we focu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
34
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 33 publications
2
34
0
Order By: Relevance
“…Clearly, Y89Q has more specificity for D-arginine. These results are consistent with the idea that the 89th amino acid is the key residue for guanidino substrate recognition [20,21].…”
Section: Amino Acid 89supporting
confidence: 82%
See 3 more Smart Citations
“…Clearly, Y89Q has more specificity for D-arginine. These results are consistent with the idea that the 89th amino acid is the key residue for guanidino substrate recognition [20,21].…”
Section: Amino Acid 89supporting
confidence: 82%
“…The predicted structure indicated that the L-or D-arginine substrate is close to L64 in the N-terminal flexible loop (GS region) and N320 on the C-terminal flexible loop. Y89, which is proposed to be the key residue for guanidino substrate recognition [20,21], is also near the substrate arginines.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, the amino acid sequence around the GS region is highly conserved in a given phosphagen kinase. Our previous studies, using Nautilus AK, Stichopus AK, Danio CK and Eisenia LK [18,[27][28][29], showed that the introduction of amino acid mutations in the GS region greatly reduced their enzymatic activity.…”
Section: Structural Basis For Catalytic Properties Of Siphonosomamentioning
confidence: 99%